Viral vectors for malaria vaccine development. - Li, S; Locke, E; Bruder, J; Clarke, D; Doolan, D; Havenga, M; Hill, A; Liljestrom, P; Monath, T; Naim, H; Ockenhouse, C; Tang, D; et al. (2007)
A workshop on viral vectors for malaria vaccine development, organized by the PATH Malaria Vaccine Initiative, was held in Bethesda, MD on October 20, 2005. Recent advancements in viral-vectored malaria vaccine development and emerging vector technologies were presented and discussed. Classic viral vectors such as poxvirus, adenovirus and alphavirus vectors have been successfully used to deliver malaria antigens. Some of the vaccine candidates have demonstrated their potential in inducing malaria-specific immunity in animal models and human trials. In addition, emerging viral-vector technologies, such as measles virus (MV), vesicular stomatitis virus (VSV) and yellow fever (YF) virus, may also be useful for malaria vaccine development. Studies in animal models suggest that each viral vector is unique in its ability to induce humoral and/or cellular immune responses. Those studies have also revealed that optimization of Plasmodium genes for mammalian expression is an important aspect of vaccine design. Codon-optimization, surface-trafficking, de-glycosylation and removal of toxic domains can lead to improved immunogenicity. Understanding the vector's ability to induce an immune response and the expression of malaria antigens in mammalian cells will be critical in designing the next generation of viral-vectored malaria vaccines.